An accurate, reliable, and universal qPCR method to identify homozygous single insert T-DNA with the example of transgenic rice - Tran, Hai Thanh; Schramm, Carly; Huynh, My-my; Shavrukov, Yuri; Stangoulis, James C. R.; Jenkins, Colin L. D.; Anderson, Peter A. (Frontiers in Plant Science, 2023)
Early determination of transgenic plants that are homozygous for a single locus T-DNA insert is highly desirable in most fundamental and applied transgenic research. This study aimed to build on an accurate, rapid, and reliable quantitative real-time PCR (qPCR) method to fast-track the development of multiple homozygous transgenic rice lines in the T1 generation, with low copy number to single T-DNA insert for further analyses. Here, a well-established qPCR protocol, based on the OsSBE4 reference gene and the nos terminator, was optimised in the transgenic Japonica rice cultivar Nipponbare, to distinguish homozygous single-insert plants with 100% accuracy. This method was successfully adapted to transgenic Indica rice plants carrying three different T-DNAs, without any modifications to quickly develop homozygous rice plants in the T1 generation. The accuracy of this qPCR method when applied to transgenic Indica rice approached 100% in 12 putative transgenic lines. Moreover, this protocol also successfully detected homozygous single-locus T-DNA transgenic rice plants with two-transgene T-DNAs, a feature likely to become more popular in future transgenic research. The assay was developed utilising universal primers targeting common sequence elements of gene cassettes (the nos terminator). This assay could therefore be applied to other transgenic plants carrying the nos terminator. All procedures described here use standardized qPCR reaction conditions and relatively inexpensive dyes, such as SYBR Green, thus the qPCR method could be cost-effective and suitable for lower budget laboratories that are involved in rice transgenic research.